Investigation of the antidiabetic and probiotic properties of lactic acid bacteria isolated from some ethnic fermented foods of Darjeeling District - Amlan Jyoti Ghosh; Supriyo Ghosh; Manab Deb Adhikari; Tilak Saha (SpringerOpen, 2024)
Abstract Background Indigenous communities residing in the Darjeeling Himalayan region and its adjacent hilly areas have a deeply rooted cultural tradition of consuming a diverse range of vegetable and milk-based fermented products, believed to confer various health advantages. With this traditional knowledge, lactic acid bacteria (LAB) were isolated from popular fermented foods such as Chhurpi (derived from Bos grunniens milk), Gundruk (made from Brassica juncea leaves), Sinki (derived from Raphanus sativus taproots), and Kinema (produced from Glycine max beans). This study aimed to investigate the probiotic properties of the prevalent LABs, including aggregation properties, bile salt hydrolase activities, survival under gastro-inhibitory conditions, safety evaluations, and their potential health-promoting attributes, with a specific focus on inhibiting α-amylase and α-glucosidase enzymes. Results Five of the LAB isolates demonstrated notable viability rates exceeding 85% when exposed to gastro-inhibitory challenges. Based on 16S rRNA gene sequencing, these isolates were identified as Pediococcus pentosaceus (isolate GAD), Lactobacillus plantarum (isolates KAD and CAD), Lactobacillus brevis (isolate SAD), and Lactiplantibacillus plantarum (isolate CMD). These LAB isolates exhibited versatile carbon source utilization, significant auto- and co-aggregation, and bile salt hydrolase (BSH) properties. Auto-aggregation capacity notably increased over time, ranging from 30 to 150 min, with percentage increments from 4.83 ± 1.92% to 67.60 ± 5.93%. L. brevis SAD displayed the highest co-aggregation increment (%) against Staphylococcus aureus, while L. plantarum KAD demonstrated potent antimicrobial activity. In vitro analyses postulated potential health benefits related to antidiabetic properties, particularly inhibiting α-amylase and α-glucosidase enzymes. L. brevis SAD exhibited the highest α-glucosidase inhibitory activity, while L. plantarum KAD displayed the most potent α-amylase inhibitory activity. Comprehensive safety assessments, including antibiotic susceptibility profiling, hemolytic activity evaluation, and in vivo acute toxicity studies, confirmed the suitability of these LAB isolates for human consumption. Conclusions The isolates show promising probiotic characteristics and significant potential in addressing metabolic health. These results carry substantial scientific implications, suggesting the pharmaceutical-based applications of these traditional fermented foods. Further in vivo investigation is recommended to fully elucidate and exploit the health benefits of these LAB isolates, opening avenues for potential therapeutic interventions and the development of functional foods.